Almonds, anchovies, + pancetta : a vegetarian cookbook, kind of - Peternell, Cal (William Morrow, an imprint of HarperCollins Publishers, 2018)
"Celebrated chef and home cook Cal Peternell likes to eat today the way people have been eating forever: with vegetables at the center of the plate, seasoned with a little bit of meat or fish to make a meal savory and satisfying. A little of the right kind of meat goes a long way, and in this book, the right ones are anchovies and pancetta, along with almonds, because nuts are the meat of the plant world. Cal uses them first for flavor, but also because it makes sense: taking savory little bites is inarguably better than big meaty mouthfuls. The salt in anchovies and pancetta draws out and enhances flavors, enriching the rest of the dish, and almonds compare favorably fat-wise and can bring a major flavor boost, especially when they're ground up. This kind of cooking is healthy, leans toward sustainability, and is economical in a way that pleases both palate and pocketbook."--Amazon.com